QUO VADIS KAJIAN MANUSKRIP JAMBI - Ali Muzakir (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
This paper discusses Jambi’s manuscripts and their potential for study. The manuscripts are not huge. The seminal manuscript has produced since the early Jambi Sultanate in the mid-17th century. Using historical and codicology perspective, this writing analyzes the origins, sources and usingthe manuscript. This research presented that Jambi’s manuscript was emerging along with the dissemination of Islam. The close link that existed between Palembang and Jambi during sultanate had influenced manuscript production.A number of Palembang manuscripts had influenced Jambi.